Evaluation of antiarthritic activity of ethanolic extract of Derris brevipes (benth.) Baker leaves - Nesni M Makkar; Veena R; Priya Mohan B.N; Jeena Ann John; Princy Louis Palatty; Kuriachan, Sanitha (Asian Journal of Medical Sciences, 2023)
Background: Derris brevipes is a common medicinal plant used in the traditional system of medicine as an anti-arthritic agent. Aims and Objectives: The present study was to evaluate the anti-arthritic activity of ethanolic extract of D. brevipes (EEDB) leaves, belonging to the family Leguminosae. Materials and Methods: The dried leaves were collected and extracted using 95% ethanol, and the extract was subjected to a preliminary phytochemical screening. In vivo activities were evaluated in collagen (chicken sternal collagen)-induced arthritis (CIA) in Sprague–Dawley rats. Prednisolone was used as the standard, and EEDB (at doses of 300 mg/kg and 600 mg/kg) was administered through the oral route. Body weight measurement, arthritic score, histological score, and radiology score assessments were carried out. Results: Preliminary phytochemical screening of leaf extract from D. brevipes showed the presence of components such as steroids, triterpenoids, and flavonoids. In vivo tests on CIA rats given the extract showed that it could lower the arthritic score, the paw volume, the radiological score, and the histological score. Conclusion: From this study, it is concluded that the D. brevipes leaf extract possesses antiarthritic activity.